Supporting Factors for Handling Slum Problems - Firdaus W Suhaeb; Ernawati S Kaseng (Pinisi Journal of Social Science, 2023)
Handling and innovative solutions due to the development of slums in urban areas that have become a problem so far that research is carried out with the aim of describing and analyzing the supporting factors of slum problems through the implementation of the City Without Slums (KOTAKU) program so that it can influence changes in community behavior at slums in Tallo District of Makassar City. The research method used is a qualitative research method with a descriptive approach. Data collection techniques use observation, interviews and documentation. Data analysis techniques use data reduction, data presentation, and conclusions. The results of this study show that several factors supporting the handling of slum problems in the implementation of the City Without Slums (KOTAKU) program build changes in urban community behavior. Communication factors, namely through the implementation of meetings between stakeholders and communities living in slum areas, such as socialization, deliberation and meetings / meetings and resulting in the emergence of agreement, support, and community anticipation in program activities. Resource factors, namely through community involvement in slum areas in the implementation of program activities, such as the community selection process based on having morale, and a sense of responsibility for the use of budgets. Disposition factors, namely the support of implementor elements in supervision and evaluation as well as being responsible and committed to the implementation of program activities to completion, transparent and making accountability reports for the implementation of activities. Then the bureaucratic structure factor, namely the existence of a tiered organizational structure at the provincial level.